Significant association and synergistic adverse prognostic effect of podocalyxin-like protein and epidermal growth factor receptor expression in colorectal cancer. Issue 1 (December 2016) - Larsson, Anna; Lehn, Sophie; Wangefjord, Sakarias; Karnevi, Emelie; Kuteeva, Eugenia; Sundström, Magnus; Nodin, Björn; Uhlén, Mathias; Eberhard, Jakob; Birgisson, Helgi; Jirström, Karin
Abstract Background Podocalyxin-like 1 (PODXL) is an anti-adhesive transmembrane protein that has been demonstrated to be an independent factor of poor prognosis in colorectal cancer (CRC). The gene encoding PODXL is located to chromosome 7, which also harbours the gene for the epidermal growth factor receptor (EGFR). The aim of this study was to examine the associations between PODXL and EGFR expression in CRC in vitro and in vivo. Methods EGFR expression was analysed in tumours from three independent patient cohorts; cohort 1 (n = 533), cohort 2 (n = 259) and cohort 3 (n = 310), previously analysed for immunohistochemical PODXL expression andKRAS andBRAF mutations (cohort 1 and 3). Levels of EGFR and PODXL were determined by western blot in six different CRC cell lines. Results High expression of PODXL was significantly associated with high EGFR expression (p < 0.001) in all three cohorts, and withBRAF mutation (p < 0.001) in cohort 1 and 3. High EGFR expression correlated withBRAF mutation (p < 0.001) in cohort 1. High EGFR expression was associated with adverse clinicopathological factors and independently predicted a reduced 5-year overall survival (OS) in cohort 1 (HR 1.77; 95 % CI 1.27–2.46), cohort 2 (HR 1.58; 95 % CI 1.05–2.38) and cohort 3 (HR 1.83; 95 % CI 1.19–2.81). The highest risk of death within 5 years was observed in patients with tumours displaying high expression of both EGFR and PODXL in cohort 1 and 3 (HR 1.97; 95 % CI 1.18–3.28 and HR 3.56; 95 % CI 1.75–7.22, respectively). Western blot analysis showed a uniform expression of PODXL and EGFR in all six examined CRC cell lines. Conclusions The results from this study demonstrate that high expression of EGFR is an independent factor of poor prognosis in CRC. Moreover, strong links have been uncovered between expression of the recently proposed biomarker candidate PODXL with EGFR expression in CRC in vivo and in vitro, and withBRAF mutation in vivo. High expression of both PODXL and EGFR may also have a synergistic adverse effect on survival. These findings suggest a potential functional link in CRC between PODXL, EGFR and BRAF, all originating from chromosome 7, which may be highly relevant in the clinical setting and therefore merit future in-depth study.